Advanced transferring of large-area freestanding graphene films by using fullerenes. (12th April 2019) - Fu, Jiye; Qiao, Yi; Song, Hang; Xu, Zheyun; Tu, Jing; Ba, Long; Lu, Zuhong
Abstract: Freestanding graphene films are desired to be widely applied in biosensor fabrication due to their distinctive physical properties and improved performance. Chemical vapor deposition has been developed to efficiently fabricate large-area graphene. However, some of the fabricated graphene films might break or be contaminated in the current transferring step using polymers. A stable and high-quality transfer method is needed. Herein, we report on an advanced transfer method of large-area graphene film which uses fullerene as a supporting substrate. Unlike polymers, which are commonly eliminated by being dissolved in an organic solution, fullerene can be easily removed by evaporation in a vacuum because it has a different heat stability to graphene. By using the improved transferring method, the percentage of integrated freestanding films after transferring was increased from 60.7% to 93.4%. The vacuum is beneficial in terms of keeping the brittle freestanding films intact. Graphene films transferred using fullerene showed an advanced flatness and a simplicial elementary composition in comparison to those transferred using polymers. Even through there is trace residue, this stable allotrope of graphene is considered to have almost no impact on biomolecule sensing. These advantages make the fullerene transferring method an attractive candidate for fabricating large-area freestanding graphene films, especially for using in the field of biochemistry analysis and biosensors.